Yizkor Books, Yiddish, and Israel - Lior Becker (Nordisk Judaistik)
Yizkor books are memorial books commemorating Jewish communities destroyed in the Holocaust, which are also the result of communal activity. The books have been published since 1943, mostly in Israel. Based on a qualitative and quantitative survey of 613 books, the largest survey of Yizkor books done to date, this article repositions the books linguistically and geographically. It demonstrates that contrary to previous research, Yizkor books are a significantly more heterogeneous phenomenon that began in the Yiddish-speaking world but quickly changed into an Israeli- and Hebrew-based phenomenon, which also included Jews from non-Yiddish-speaking Ashkenazi, and even Sephardic, communities. Especially since the 1980s, the phenomenon further evolved to include more English-language books, published in the USA. Against this geographical and linguistic backdrop, I also show that the producers of the books were a diverse array of groups and individuals from varying backgrounds. The publishers were not only Yiddish-speaking landsmanschaftn (Jewish mutual-aid societies consisting of individuals originating from a particular place and their descendants) but a variety of organizations of different kinds, individuals, and even schoolchildren. Finally, I present examples of Yizkor books that were presented in previous research as landsmanschaft literature produced by Holocaust survivors and show that these assumptions regarding the authors are partially or wholly erroneous and that those books were, in fact, produced by a different set of actors.